Investigation of the Gas-Phase Reaction of Nopinone with OH Radicals: Experimental and Theoretical Study - Gisèle El Dib; Angappan Mano Priya; Senthilkumar Lakshmipathi (Atmosphere, 2022)
Monoterpenes are the most essential reactive biogenic volatile organic compounds. Their removal from the atmosphere leads to the formation of oxygenated compounds, such as nopinone (C9H14O), one of the most important first-generation β-pinene oxidation products that play a pivotal role in environmental and biological applications. In this study, experimental and theoretical rate coefficients were determined for the gas-phase reaction of nopinone with hydroxyl radicals (OH). The absolute rate coefficient was measured for the first time using a cryogenically cooled cell along with the pulsed laser photolysis–laser-induced fluorescence technique at 298 K and 7 Torr. The hydrogen abstraction pathways were found by using electronic structure calculations to determine the most favourable H-abstraction position. Pathway 5 (bridgehead position) was more favourable, with a small barrier height of −1.23 kcal/mol. The rate coefficients were calculated based on the canonical variational transition state theory with the small-curvature tunnelling method (CVT/SCT) as a function of temperature. The average experimental rate coefficient (1.74 × 10−11 cm3 molecule−1 s−1) was in good agreement with the theoretical value (2.2 × 10−11 cm3 molecule−1 s−1). Conclusively, the results of this study pave the way to understand the atmospheric chemistry of nopinone with OH radicals.